High strength and ductile fibrous concrete of enhanced fire resistance - Lourenço, Lúcio (2007)
In the present work a Fiber Reinforced Concrete of Enhanced Fire Resistance (FRCEFR) was developed and its properties are characterized by experimental research. This concrete is intended to have enough resistance for the most structural engineering applications and is reinforced with a fibrous system to assure the necessary ductility and to improve its fire resistance. Two types of fibers are used to accomplish the aforementioned requisites for the concrete. The research performed for the selection of a nonmetallic fiber type for inclusion on the FRCEFR is resumed. The experimental programs carried out to evaluate the residual compressive and flexural behavior of the developed FRCEFR are presented and the main obtained results are analyzed. The tests were executed at 28 days after FRCEFR have been exposed to the following distinct levels of temperature: 250ºC, 500ºC, 750ºC and 1000ºC.